EXAMINING GENDER-BASED INCLUSIVE EDUCATIONAL INTERVENTIONS IN THE KADJEBI DISTRICT, GHANA - Agbenyo, F.; Sarkpoh, F. (UDS International Journal of Development, 2022)
Reports from various evaluations of the Millennium Development Goal (MDG) 2 indicate that even though a great deal of success had been chalked, a lot more was yet to be attained. In 2013, just two years to 2015, which marked the end of the MDG target year, the Kadjebi District was declared a deprived district in terms of education. The paper employed the lenses of social exclusion/inclusion and theory of change. It examined the extent of gender participation in and achievement of other results of education development interventions, now derived from the Sustainable Development Goal (SGD) 4. Basically, the paper used quantitative data from a secondary source after the Kadjebi District was selected from a group of six deprived districts, using a simple random sampling technique. It emerged that Kadjebi is faring well in terms of interventions targeting access to JHS and SHS education by gender but not much progress in the area of indicators measuring quality of education. It is recommended that all stakeholders, particularly, NGOs that were undertaking the interventions, collaborate to diagnose the factors militating against achievement of the quality objective of their interventions and dwell on their respective competitive advantage to create the necessary synergies to be able to tackle these challenges head-on in the District. Key Words/Descriptors: Education Intervention, Gender, World Bank, Sustainable Development Goals, Ghana.